URDU-A RESEARCH ANALYSIS IF MAKING ROWS (SAF) FOR THE CONGREGATIONAL PRAYER WITH REFERENCE TO COVID-19 - Naeem Pasha; Ata ur Rahman (دی اسکالر)
Making and properly straightening of rows (Saf) is integral part of congregational prayers. The rows can either be physically jointed or can be implied in case people have to stand in a distance for example people offering prayer inside and outside the prayer hall. The important thing is to be under proper discipline while making rows for prayer. There should not be any unnecessary gap in the rows. But it is permitted in case if inevitability. Unnecessary gap is considered to be Tahrim Takrihi. Now a days it has emerged as a big issue in wake of the prevailing Pandemic; COVID-19. Scholars  are if the opinion that it us not only permitted to observe medical instruction while making rows for prayer but it is the desired and suggested option under the circumstances. This is because the current Pandemic can speedily spread in case social distancing is not practiced. The current article will focus on this issue in detail.